Wireless structural health monitoring system by capacitor sensing technique - Alam, A. H. M. Zahirul; Che Mustapha, Nurul Arfah; Amir Hassan, Noor Syamira Asyiqin; Islam, Md. Rafiqul; Khan, Sheroz; Azman, Amelia Wong; Eusuf, Muhammad Abu (World Scientific, 2017)
Structural health monitoring (SHM) is a method of localizing damage in infrastructures regarding structural strain, vibration or movements due to external contributing factors which mainly occur as a result of natural disasters. The need to analyze such occurrences can prevent potential damage of massive scale. A sensing system with high sensitivity is needed for reliable structural health monitoring. A capacitive sensing circuit is designed using off-the-self-components and transmit data wirelessly using XBee. The circuit can detect small changes of capacitance variation due to structure vibration.